Decannulation protocol for short term tracheostomy in pediatric head and neck tumor patients. (February 2022) - You, Peng; Dimachkieh, Amy; Yu, Justin; Buchanan, Edward; Rappazzo, Christina; Raynor, Tiffany; Arjmand, Ellis; Bedwell, Joshua; Weber, Randal S.; Kupferman, Michael E.; Chelius, Daniel C.
Abstract: Background: While the majority of pediatric tracheostomies are performed in the setting of chronic and complex medical comorbidities, perioperative tracheostomies following head and neck tumor ablation are generally short-term. Deliberate planning is required for decannulation in this setting and no published protocols currently exist. Our study outlines a management strategy for short-term tracheostomy in pediatric patients following head and neck surgery. Methods: A retrospective study of pediatric head and neck tumor patients undergoing tracheostomy was performed at a quaternary children's hospital from February 1, 2016 to December 31, 2018. Charts were reviewed for demographics, surgical operation, relevant tracheostomy-related complications, and time to decannulation. Results: Eleven patients with a mean age of 10.4 years (st.dev. 6.7, range: 0.5–23) underwent tracheostomy during their primary ablative/reconstructive surgery. Trans -tracheal pressure monitoring helped direct the need for tracheostomy downsizing and readiness for capping trials. All patients were decannulated before hospital discharge after a mean of 12.8 days (st.dev. 2.5, range: 9–18) and were discharged after a mean of 14.8 days (st.dev. 2.5, range: 11–20). Conclusion: Pediatric head and neck surgery patients can be quickly and safely decannulated with an instructive protocol and multidisciplinary care. Highlights: Decannulation in pediatric patients is challenging. Tracheostomies following head and neck tumor ablation are generally short-term. A step-wise protocol to decannulate short-term pediatric tracheostomy is described. Trans -tracheal pressure and deliberate planning allow successful decannulations.